Theoretical Views on the Legal Nature and Legal Structure of the Contract for the Carriage of Goods by Sea in Scientific Works of the Early Twentieth Century - A. Kh. Khabibulaev (Теоретическая и прикладная юриспруденция)
The issues of determining the legal structure of legal institutions have always been acute in the doctrine. The article deals with the theoretical concepts of the contract for the carriage of goods by sea at the beginning of the 20th century. It is noted that all the studied positions of scientists have a certain value and significance. According to the author, despite the fact that the main provisions of the contract in question were reflected precisely in the civil legislation of that period, it represented an independent, unique, complex type of sui generis contract. The paper shows the importance of theoretical study of the contract for the carriage of goods by sea in a historical context and its influence on the evolution of domestic legislation.